Development of miRNA-Based Approaches to Explore the Interruption of Mosquito-Borne Disease Transmission - Xu, Tie-Long; Sun, Ya-Wen; Feng, Xin-Yu; Zhou, Xiao-Nong; Zheng, Bin (Frontiers in Cellular and Infection Microbiology, 2021)
MicroRNA (miRNA or miR)-based approaches to interrupt the transmission of mosquito-borne diseases have been explored since 2005. A review of these studies and areas in which to proceed is needed. In this review, significant progress is reviewed at the level of individual miRNAs, and miRNA diversification and relevant confounders are described in detail. Current miRNA studies in mosquitoes include four steps, namely, identifying miRNAs, validating miRNA-pathogen interactions, exploring action mechanisms, and performing preapplication investigations. Notably, regarding the Plasmodium parasite, mosquito miRNAs generally bind to mosquito immunity- or development-related mRNAs, indirectly regulating Plasmodium infection; However, regarding arboviruses, mosquito miRNAs can bind to the viral genome, directly modifying viral replication. Thus, during explorations of miRNA-based approaches, researchers need select an ideal miRNA for investigation based on the mosquito species, tissue, and mosquito-borne pathogen of interest. Additionally, strategies for miRNA-based approaches differ for arboviruses and protozoan parasites.